Co-Effects of Graphene Oxide and Cement on Geotechnical Properties of Loess - Dongbo Li; Pengbo Lei; Hongchi Zhang; Jiaping Liu; Wei Lu (Advances in Materials Science and Engineering)
Improvement of geotechnical properties of soil by cementitious additives and nanomaterials is commonly used method. However, few systematic research studies on the co-effects of them on the geotechnical properties of loess have been explored. In the present research, the enhancement technique of loess was proposed based on the co-effects of graphene oxide (GO) and cement. In addition, the compactability, mechanical properties, water resistance, and microstructure of the GO/cement/loess ternary system were studied. The results revealed that, with the increase of incorporation of GO (0.03, 0.06, 0.09, and 0.12 wt. %), the optimum moisture decreased, while the dry density, mechanical properties, and water resistance increased significantly. And an optimum GO content of 0.09 wt. % was determined according to mechanical properties and water resistance. Moreover, the scanning electron microscope (SEM) results revealed that the microstructure was densified and the characteristics of pores were refined. And the co-work mechanisms of GO/cement on loess were summarized. All the results indicated that the GO/cement mixture has remarkable co-effects on the geotechnical properties of loess.